Strategi Pembangunan Ekonomi Desa Kutuh sebagai Desa Mandiri di Kabupaten Badung, Bali - Tegar Prasetyo Nugroho; Siti Hana Titasari; Raditya Arva Pradipa; Pipit Trisnia Mayangsari; Karina Mujiono; Almahdy Ardinsah; Sugiantoro; Nurul Hasanah (Jurnal Pendidikan Ekonomi Undiksha, 2025)
The abstract version of the English is written using the English version of the British in past tense and appropriate sentences. The result and conclusions are written in the form of the present tense. Abstracts are expected to be more communicative and not monotonous. A simple sentence is English contains a minimum of subject and predicate elements This study aims to analyze the application of sustainable economic principles and the role of the village government in supporting the achievement of Sustainable Development Goals (SDGs) point 8 in Kutuh Village, South Kuta District, Badung Regency, Bali. The research employed a qualitative descriptive approach with data collected through in-depth interviews, direct observation, and documentation. The subjects involved the village head, BUMDes (Village-Owned Enterprise) managers, local residents, and visitors. The findings indicate that the village government, through BUMDes Kutuh, manages various business units such as modern waste recycling, Pertashop, advertising boards, tourism villas, and multipurpose halls. These enterprises not only increase the village's original revenue (PAD) but also significantly absorb local labor. The BUMDes management strategy is based on inclusiveness and sustainability, adopting local values such as Tri Hita Karana. In addition to creating decent jobs, the village strives to ensure that economic development is participatory and long-term oriented. This study suggests that the success of Kutuh Village in developing a self-sustained rural economy can serve as a replicable model for other villages in Indonesia seeking to implement sustainable, locally driven economic development.